Activation of estrogen-responsive genes does not require their nuclear co-localization. - Silvia Kocanova; Elizabeth A Kerr; Sehrish Rafique; Shelagh Boyle; Elad Katz; Stephanie Caze-Subra; Wendy A Bickmore; Kerstin Bystricky (PLoS Genetics)
The spatial organization of the genome in the nucleus plays a role in the regulation of gene expression. Whether co-regulated genes are subject to coordinated repositioning to a shared nuclear space is a matter of considerable interest and debate. We investigated the nuclear organization of estrogen receptor alpha (ERalpha) target genes in human breast epithelial and cancer cell lines, before and after transcriptional activation induced with estradiol. We find that, contrary to another report, the ERalpha target genes TFF1 and GREB1 are distributed in the nucleoplasm with no particular relationship to each other. The nuclear separation between these genes, as well as between the ERalpha target genes PGR and CTSD, was unchanged by hormone addition and transcriptional activation with no evidence for co-localization between alleles. Similarly, while the volume occupied by the chromosomes increased, the relative nuclear position of the respective chromosome territories was unaffected by hormone addition. Our results demonstrate that estradiol-induced ERalpha target genes are not required to co-localize in the nucleus.